Fanconi anemia: in all its glory - Rai, Rajesh; Lahiri, Keya; Gahlowt, Pallavi; Chugh, Vasundhara; Bhattar, Anand (International Journal of Research in Medical Sciences, 2017)
Fanconi Anemia (FA) is a rare autosomal recessive disorder affecting multiple body systems. The diagnosis is based on morphological abnormalities, hematological abnormalities (pancytopenia, macrocytic anemia & progressive bone marrow failure) and genetic testing. However, genetic testing is complicated for FA because there are often many genes that are associated with its development, and large duplications, deletions or sequence variations are frequently observed in some of these genes. We report a patient with cytogenetically confirmed Fanconi anemia. Although morphological abnormalities were present from birth, diagnosis was suspected and made at 8 years of age when he presented to us. We report this case to create awareness among clinicians to use modern modalities of diagnosis for such cases in addition to the clinical assessment. This would further help these children reach their adulthood with good quality of life.